Uji Efektivitas Rizobakteri sebagai Agen Antagonis terhadap Fusarium oxysporum f.sp. capsici Penyebab Penyakit Layu Fusarium pada Tanaman Cabai Rawit (Capsicum frutescens L.) - KOMANG ADI MAHARTHA; KHAMDAN KHALIMI; ALIT SUSANTA WIRYA GUSTI NGURAH (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2013)
ABSTRACT Effectiveness Test of Rhizobacteria as Antagonist Agents against Fusarium oxysporum f.sp. capsici Causes Fusarium Wilt Disease in Chili Pepper Plants(Capsicum frutescens L.) Utilization of rhizobacteria as antagonist agents Fusarium oxysporum f.sp. capsici was recommended. The objectives of this research were conducted to evaluate the effectiveness of rhizobacteria as an agents of biocontrol. F. oxysporum f.sp. capsici was put in the center of PDA medium (control). Rhizobacteria as antagonistic fungus was inoculated four side onto PDA medium and then F. oxysporum f.sp. capsici was put in the center of PDA medium. Result of this research, Klebsiella pneumoniae isolates KTNA2 showed strong inhibitory activity against F. oxysporum f.sp. capsici. Percentage of inhibitory activity at 89,65%. Aplication of Pantoea agglomerans isolates GTA24, Stenotrophomonas maltophilia isolates KTTA4, Klebsiella pneumoniae isolates GSA6, and Klebsiella pneumoniae isolates KTNA2 in the open field could suppress the disease incidence about 33,33%, 43,33%, 56,67%, and 63,33% respectively. The disease incidence on control about 80%. Keywords: rhizobacteria, antagonist agents, and Fusarium oxysporum f.sp. capsici